ROLE OF RARE-EARTH METALS AT MODIFYING OF IRON-BORON ALLOY - N. F. Nevar (Литьë и металлургия)
The technology of input of rare-earth metals in iron-boron alloy is developed and influence of conditions of input on characteristics of product metal is investigated.